(untitled) (Research, Society and Development, 2021)
The present work consists of a bibliometric survey on medicinal plants with larvicidal/insecticide potential and/or used as repellents in Aedes ssp., and to verify the quantity of scientific works in the control of arboviruses in a 10-year interval. The research was delineated through bibliometric analysis, whose data were obtained from the Web of Science, PubMed Central: PMC, LILACS and MEDLINE Complete databases. After all the refinements of the keywords searched in the scientific databases in the period from 2011 to 2020, the best results were obtained with "Aedes" and "Insecticidal" and "plants", PubMed Central: PMC in first with 1156 articles, in sequence to Web of Science with 119, MEDLINE Complete with 10 and LILACS 06. No records were found of works published in Brazil with "Aedes" and "ethnobotanical" and in the sequence "Aedes" and "Insecticidal" and "plants" came first and in the other researched topics ranked second, losing to the United States of America. It is concluded that the bibliometric survey of scientific papers with the terms "Aedes" and "Insecticidal" and "plants" stood out not only for the quantity in the 10-year series more for approaching similar researches, mainly of ethnobotanical surveys to combat arboviruses, with which we intend to carry out with these descriptors.